“But it didn’t ruin me”: a feminist phenomenological analysis of trauma and healing after intimate partner violence - McAllister, Paige (Kansas State University, 2022)
Intimate partner violence (IPV) is a common problem especially for racial and ethnic minority women and gender and sexual minority individuals. The current research on trauma and healing after IPV does not always represent the diversity of those most likely to experience IPV which is problematic as because the impacts of interpersonal and structural violence are related to and impacted by the other. This lack of attention to diverse experiences is also reflected in the systems in place to aid survivors of IPV including using models of trauma and healing that fail to account for the impacts of both structural and interpersonal violence. Therefore, understanding the lived experience of trauma and healing after IPV with a diverse sample from a critical feminist lens would be valuable to those in helping professions. In this study, interviews were conducted with 16 survivors of IPV. Using a feminist phenomenological analysis, several themes were identified that detailed the physical, psychological, and emotional wounds that occurred because of IPV (wounding systems, sexual/gender identity weaponized by partner, marginalization as a wound, impact of IPV on children), the physiological, emotional, and behavioral reactions to those wounds (PTSD symptoms, romantic relationship impacts, sexual difficulties, impact on view of self and experience), and how survivors conceptualize their own healing process (healing systems, healthy romantic relationships, working through triggers, advocating for self and others, healing as a process). Clinicians working with survivors of IPV should expand their assessment of trauma beyond PTSD criteria and focus on relational healing in their client’s relationships and in the therapy room.
Keywords: Intimate partner violence; Trauma; Healing